Physical Quality of the Eggs of Mamoa Bird (Eulipoa wallacei - Y. Sapsuha (Jurnal Ilmu dan Teknologi Peternakan, 2013)
The objective of the sudy was to determine the physical characteristics of the eggs of Mamoa bird which includes several components, namely weight, shape, shell color, length, diameter, egg index, percentage of egg white (albumen), percentage of yolk (yolk), eggshell weight, Haugh unit (HU), and the thick shell. Based on the results and discussion, it concluded that the average egg weight of 98.17 ± 7.78 g birds Mamoa . Comparison of yolk, albumen and shell was 68.37 ± 2.55%, 23.82% ± 2.61 and 7.82 ± 0.31%, while the value of HU was 69.42 ± 3.55.